2020
DOI: 10.1136/bmjsem-2020-000874
|View full text |Cite
|
Sign up to set email alerts
|

Thigh-worn accelerometry for measuring movement and posture across the 24-hour cycle: a scoping review and expert statement

Abstract: IntroductionThe Prospective Physical Activity Sitting and Sleep consortium (ProPASS) is an international collaboration platform committed to harmonise thigh-worn accelerometry data. The aim of this paper is to (1) outline observational thigh-worn accelerometry studies and (2) summarise key strategic directions arising from the inaugural ProPASS meeting.Methods(1) We performed a systematic scoping review for observational studies of thigh-worn triaxial accelerometers in free-living adults (n≥100, 24 hours monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 121 publications
0
44
0
Order By: Relevance
“…Such studies would ideally utilize both self‐reported and device‐based measures of PA (e.g., accelerometers) so that we better understand the influence of each complex dimension of physical activity (domain, frequency, total volume, etc. ) 87 on TL.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies would ideally utilize both self‐reported and device‐based measures of PA (e.g., accelerometers) so that we better understand the influence of each complex dimension of physical activity (domain, frequency, total volume, etc. ) 87 on TL.…”
Section: Discussionmentioning
confidence: 99%
“…However, depending on the research questions, it may be enough to apply a single accelerometer on the thigh or lower back to record most key physical activity types. If the primary research question is related to assessment of "time-on-feet" (standing) and physical activity (walking, running, and cycling), applying a single thighworn accelerometer can be enough (Crowley et al, 2019;Stevens et al, 2020). However, if the main purpose is to study sedentary behaviors and a necessity of differentiating between lying down and sitting, a back-worn accelerometer is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity zones (sleep, SP, LPA, MVPA) represent only one dimension of 24-hour movement behaviour [ 47 ]. Other dimensions include posture/activity type (reclining, sitting, standing, walking, running, cycling, and walking stairs), bout duration (short, moderate, or long), domain (sleep, work/school, and non-work), and biological state (awake or asleep) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%